Identification Types of the Marine Debris and Factors Related them in Semarang City - Amanda Hesti Pratiwi; Budiyono Budiyono; Nikie Astorina Yunita Dewanti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Beach waste pollution can have an impact on human health in these areas. Beach waste data is needed to determine the solution for preventing beach/marine pollution. This study aims to estimate beach waste density, identify types of beach waste and factors of beach waste distribution in Semarang. The method used was descriptive observational with a cross-sectional research design. The sample was determined by purposive sampling and available 7 points of beach spread over four districts at Semarang. Beach waste samples took at each beach along 100m the width adjusts to the beach's width. The highest beach waste was found on Baruna Beach (North Semarang), with a total of 3,243 waste (227.4 kg). Moreover, the lowest beach waste was found on Mangkang Kulon (Tugu), with a total of 711 pieces of waste (63kg). From the 7 sample points of the beach, the average density of waste is 5.3 kg/m². Most waste types are plastics and woods. The different levels of waste on the beach area due to wind patterns and tidal conditions. This study's conclusion is the dominant factors of the beach waste levels are the pattern of wind, seawater currents, and density of river flow waste, while population density and urban economic growth affect the level of the city solid waste.